Effects of polarity parameter on the machining of tool steel workpiece using electric discharge machining (EDM) - Ahmad Fadzil, Mohamad (2009)
Electrical discharge machining (EDM) has been recognized as an efficient production method for precision machining of electrically conducting hardened materials. The most important in this study is the effect of the polarity on the machining tool steel work piece using electrical discharge machining to the material removal rate, electrode wear and surface roughness. The objectives of this study are investigate the effects of polarity to the material removal rate (MRR), electrode wear and surface roughness (SR) on the machining of tool steel work piece using Electric Discharge Machining (EDM), determine the optimum condition using orthogonal arrays and response graph, determine the most significant and significant factor using ANOVA and F-test. The problem of this study is how to choose between electrode and work piece as a terminal positive or terminal negative. The wrong polarity can have significant implications on speed, wear, and stability. The design of experiment that use in this experiment is L18 orthogonal arrays. The most important of the output parameters are material removal rate, electrode wear and surface roughness. From the data obtained, the Microsoft Excel will be use to determine the optimum parameters and the most significant factors. Finalize of the study is discuss the effects of polarity to the material removal rate, electrode wear and surface roughness.